HUMOR DALAM PERSPEKTIF HADIS TEMATIK - Muhammad Faris; Muhammad Alif (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Humor is one aspect of the Prophet Muhammad’s communication that frequently appears in hadiths but is often understood partially and rarely examined through a thematic approach. This article aims to analyze humor from the perspective of hadith by exploring its forms, ethical boundaries, and impacts using a thematic hadith methodology. This study employs a qualitative approach with library research as its main method. Data were collected from primary hadith compilations through thematic searching using keywords related to humor and were analyzed through classification and content interpretation techniques. The findings indicate that the Prophet’s humor appears in two main forms: verbal and nonverbal. Verbal humor is manifested through expressions, wordplay, and rhetorical language that carry educational and empathetic values, while nonverbal humor is expressed through facial expressions, smiles, laughter, and actions reflecting relational warmth. Moreover, the hadiths establish clear ethical guidelines for humor, including the prohibition of lying, humiliating others, causing harm, and excessive laughter. In terms of impact, humor practiced in a proportional manner contributes positively to emotional balance, social harmony, and the quality of interpersonal interactions. Therefore, humor in the perspective of hadith represents an integral part of prophetic communication ethics and can serve as a normative reference for contemporary social humor practices.